EFEKTIVITAS PELAYANAN ADMINISTRASI KEPADA MASYARAKAT DI KANTOR DESA SUMBERSALAK KECAMATAN LEDOKOMBO JEMBER - Ahmad Haris Sya’roni (PT. Hasba Edukasi Mandiri, 2025)
Administrative service is a vital function of the village government in realizing good governance and improving community welfare. Service effectiveness is crucial in determining community satisfaction and the image of the village government. This study aims to analyze the effectiveness of administrative services at the Sumbersalak Village Office, Ledokombo District, Jember Regency, and to identify the supporting and inhibiting factors during its implementation. The research method used is descriptive qualitative. Data was collected through interviews with village officials and the community, direct observation, and documentation. Data validity was tested using triangulation, and data analysis utilized the Miles and Huberman model (data reduction, data display, and conclusion drawing). The results indicate that administrative services at the Sumbersalak Village Office are generally quite effective. Village officials understand the service procedures, demonstrate a friendly attitude, and strive to provide clear, fast, and transparent services. Supporting factors include the officials' awareness in performing their duties, the existence of clear rules and procedures, and the staff's ability and skills in serving the public. However, service effectiveness is still hindered by the low discipline of some employees, insufficient socialization of service procedures to the public, and limited facilities/infrastructure (such as waiting rooms and nursing rooms). The conclusion suggests that although administrative services meet basic public service principles, improved staff discipline, expanded community socialization, and provision of adequate facilities are necessary to achieve optimal, fair, and equitable service.